2017
DOI: 10.3952/physics.v57i2.3515
|View full text |Cite
|
Sign up to set email alerts
|

Time delay of radiation from pulsar in a binary system that moves in field of Schwarzschild black hole

Abstract: A compact binary star that moves in a strong external gravitational field of a Schwarzschild black hole is considered. Decomposition of the redshift into a series with respect to the size of the binary system is obtained. This expression is used to calculate the redshift for a model binary system. Possible application of the results is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…However, the influence of the gravitational field on the propagation of light was neglected. In our previous paper [30], we showed that the last effect must also generally be taken into account. Unlike the cited papers, our works use fully generally relativistic approaches in calculations.…”
Section: Introductionmentioning
confidence: 90%
“…However, the influence of the gravitational field on the propagation of light was neglected. In our previous paper [30], we showed that the last effect must also generally be taken into account. Unlike the cited papers, our works use fully generally relativistic approaches in calculations.…”
Section: Introductionmentioning
confidence: 90%